The Association Between FT3 With the Outcome and Inflammation/Coagulopathy/Fibrinolysis of COVID-19 - Deng, Jiayi; Zhang, Siye; Peng, Fei; Zhang, Quan; Li, Yi; Zhong, Yanjun (Frontiers in Endocrinology, 2022)
1.1 Background: Coronavirus disease 2019 (COVID-19) pandemic has caused substantial threats to people’s physical health and lives, claiming the lives of over 5 million people worldwide. It is imperative to identify the disease severity and intervene with effective therapy as early as possible. Previous studies have shown that low free triiodothyronine (FT3) may possess the predictive value on COVID-19 prognosis. 1.2 Methods: In this retrospective cohort study, 15-day clinical and laboratory data of 186 hospitalized patients of COVID-19 after admission were analyzed. Groups were based on the disease severity of COVID-19, survival or non-survival, and presence or absence of euthyroid sick syndrome (ESS). Categorical variables were compared with the chi-square test or Fisher’s exact test. Continuous variables were tested by Wilcoxon rank-sum test for the non-normal distribution. Spearman correlations were used to assess the correlations between FT3 with clinic parameters of multiple time points. 1.3 Results: The non-survival patients had significant lower levels of FT3 (3.24 ± 0.42 vs 4.19 ± 0.08 pmol/L, P < 0.05) and thyroid-stimulating hormone (TSH) (0.69 ± 0.19 vs 2.32 ± 0.2 uIU/mL, P < 0.05), and the FT3 of severe patients was significantly lower than that of non-severe (3.67 ± 0.14 vs 4.33 ± 0.09 pmol/L, P < 0.05). Fifty-nine cases of COVID-19 patients were diagnosed with ESS. Compared with non-ESS patients, those with ESS were older and had higher proportions of fever, shortness of breath, hypertension, diabetes, severe disease, and mortality. In addition, the correlation analysis between FT3 and clinic parameters showed that FT3 were positively related to the lymphocyte count and albumin, and negatively correlated with C-reactive protein, erythrocyte sedimentation rate, and D-dimer at all time points in the first 15 days after admission. 1.4 Conclusion: Low FT3 had a significant predictive value on the prognosis of COVID-19 patients and FT3 was significantly related with clinic parameters of inflammation/coagulopathy/fibrinolysis.